The conditions for the emergence of schizophrenia - Adam Pawlak; Grzegorz Wosik (Kazimierz Wielki University, 2019)
The work presents genetic, biological and psychological determinants of schizophrenia . Current knowledge about the etiopathogenesis of schizophrenia is incomplete and unclear, which determines scientists to conduct further research to thoroughly understand the causes of this disease. Understanding all conditions of schizophrenia can undoubtedly result in more effective treatment of patients in the future, prolonging remission periods and improving the quality of life of patients and their families.